THE PHASE-DIAGRAM OF A GENERALIZED XY MODEL - Carpenter, D; Chalker, J (1989)
A generalisation of the two-dimensional XY model is studied using Monte Carlo simulation. In this model, two-component classical spins interact both ferromagnetically and nematically. Three phases occur as temperature and the two interaction strengths are varied: a high-temperature, disordered phase, and two low-temperature phases with algebraic correlations in, respectively, the ferromagnetic and nematic order parameters. The critical behaviour at the phase boundaries is examined: the high-temperature phase is entered via Kosterlitz-Thouless transitions, whilst the low-temperature phases are separated by an Ising transition.